The Policy Measures Impact on EU Beekeeping - Gheorghe Adrian ZUGRAVU; Constanta Laura AUGUSTIN (ZUGRAVU); Maria Magdalena TUREK RAHOVEANU; Loredana DIMA; Ciprian Petrisor PLENOVICI (Communications of International Proceedings, 2020)
The aims of this paper are to analysis impact of potential of EU policy measures for beekeeping. The agricultural policy measures related to technical assistance in beekeeping have decisively contributed to the increase of productivity and quality. The result of applying these measures to the beekeeping sector was an essential contribution to stabilizing honey production in the EU, which was achieved by increasing productivity and quality.
Keywords: Beekeeping; Agricultural Policy